Ablation of Supraventricular Arrhythmias With as Low as Reasonably Achievable X-Ray exposure (AALARA): Results of Prospective, Observational, Multicenter, Multinational, Open-Label Registry Study on Real World Data Using Routine Ensite 3D Mapping During SVT Ablation - Amin, Mohammad; Abdrakhmanov, Ayan; Kropotkin, Evgeniy; Traykov, Vasil; Salló, Zoltán; Gellér, László; Lorgat, Faizel; Sapelnikov, Oleg; Toman, Ondrej; Al-Muti, Khalid; Aljaabari, Mohamed; Bystriansky, Adrian; et al. (Pacing and clinical electrophysiology, 2024)
INTRODUCTION: The reduction of fluoroscopic exposure during catheter ablation of supraventricular arrhythmias is widely adopted by experienced electrophysiology physicians with a relatively short learning curve and is becoming the standard of care in many parts of the world. While observational studies in the United States and some parts of Western Europe have evaluated the minimal fluoroscopic approach, there are scarce real-world data for this technique and the generalizability of outcomes in other economic regions. METHOD: The AALARA study is a prospective, observational, multicenter, and multinational open-label study. Patients were recruited from 13 countries across Central Eastern Europe, North and South Africa, the Middle East, and the CIS (Commonwealth of Independent States), with different levels of operator expertise using minimal fluoroscopic exposure techniques. Data on radiation exposure, procedural success, complications, recurrence, and quality of life changes were collected and analyzed. RESULT: A total of 680 patients were enrolled and followed for 6 months. The majority were ablation naïve with the commonest arrhythmia ablated being typical AVNRT (58%) followed by Atrial Flutter (23%). Zero fluoroscopy exposure was observed in almost 90% of the cases. Fluoroscopy was most commonly used during the ablation phase of the procedure. We observed a high acute success rate (99%), a low complication rate (0.4%), and a 6-month recurrence rate of 3.8%. There was a significant improvement in the patient's symptoms and quality of life as measured by patient global assessment. CONCLUSION: The routine use of a 3D mapping system during right-sided ablation was associated with low radiation exposure and associated with high acute success rate, low complications, and recurrence rate along with significant improvement in quality of life. The data confirm the reproducibility of this approach in real-world settings across different healthcare systems, and operator experience supporting this approach to minimize radiation exposure without compromising efficacy and safety. TRIAL REGISTRATION: NCT04716270.
Keywords: zobrazování trojrozměrné; Tachycardia, Supraventricular; fluoroskopie; Evropa; Catheter Ablation; lidé středního věku; kvalita života; Europe; Radiation Exposure; radiační expozice; ženské pohlaví; lidé; Prospective Studies; mužské pohlaví; katetrizační ablace; Registries; registrace; Humans; Fluoroscopy; Imaging, Three-Dimensional; Quality of Life; prospektivní studie; Female; Middle Aged; supraventrikulární tachykardie; Male